If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 + -2x + 1 + -6 + -4 = y Reorder the terms: 15 + 1 + -6 + -4 + -2x = y Combine like terms: 15 + 1 = 16 16 + -6 + -4 + -2x = y Combine like terms: 16 + -6 = 10 10 + -4 + -2x = y Combine like terms: 10 + -4 = 6 6 + -2x = y Solving 6 + -2x = y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -2x = -6 + y Combine like terms: 6 + -6 = 0 0 + -2x = -6 + y -2x = -6 + y Divide each side by '-2'. x = 3 + -0.5y Simplifying x = 3 + -0.5y
| (10+8)*8-6=x | | Graphy=7 | | 10x-3x+96=10x+45 | | x^2+3x-17=1 | | (1/4)*(2/3) | | i+12=4 | | 60-5p=30+p | | u=(8n+31)+5(n+1) | | 10b+2-12=b+50 | | 3x+9=6x+(3) | | (2x-9)=(27-4x) | | Y^5/y^3 | | 7*5*(2-3)=x | | jp=irt | | -2(12-12n)=6(2n-10) | | 5(3d-2)+4d=2(2d+1)-3d | | 0=2+2x-4x^2 | | (2x-9)-(27-4x)=180 | | 2r+(5-r)=13+2r | | 5y+y=-14 | | -10=5a | | -3(-4w+1)+15=13w | | 5(x+1)+7=7x | | sr+t=u | | 14=-l/4 | | 19= | | -6(b+7)=-7b-37 | | -3(-4w+1)+15=13 | | 4=2(u-4)-8u | | 12.48+0.11=13.23+0.09 | | 8x-4y=-20 | | 21+2(21+3)+(4*21-5)=c |